Corporate creativity : - Robinson, Alan G. (Berrett-Koehler Publishers, 1997)
Corporate Creativity consistently connects creative outcomes to the actions that really made a difference to them. Through detailed real-life examples from organizations around the world - including British Airways, Du Pont, Fujitsu, General Motors, Hallmark, Hewlett-Packard, IBM, Japan Railways East, Kodak, Universal Studios, the United States Forest Service, and enterprises in the USSR - the authors show how improvements and breakthroughs actually happen in organizations.